Perancangan Sistem Pengambilan Keputusan Minat Jurusan Siswa Sman 1 Matur Berbasis Web - Zuhari, Rahmanda; Zahmi, April; Saputra, Roni (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Progress in various fields of technology, especially advances in information technology and computers, encouraging the emergence of new innovations in the presentation of information to meet the needs of information. As a tool of man, the computer also has advantages such as speed, accuracy and efficiency of data processing as compared to manual systems. In the case of SMAN 1 Matur still many systems are still done manually, including the majors interests of students, where the weaknesses of the current system is the amount of use of paper for printing questionnaires charging interest and talent for each student. Long process of distribution of questionnaires from teachers to students, after students filled in questionnaires, the questionnaire must be returned to the teacher to be processed in order to get the interest and talent, only then accepted by the students. Thus it will be in designing a new system of student data processing system before using the questionnaire into a web-based application that can encapsulate student data thus simplifying the decision granting the interest and talent of students of SMAN 1 mature.